Impact of GnRH Analogues and Exogenous Progesterone Supplementation in Treatment of Ovarian Inactivity for Primiparous and Multiparous Dromedary She-Camels in Egypt - Ghallab, Rezk Said; Rashad, Amr; Abumandour, Mohamed M.A. (Journal of Advanced Veterinary Research, 2022)
The present investigations were designed to deal with the problem of ovarian inactivity of Dromedary camel. Twenty she-camels were divided into two equal groups as primiparous or multiparous. The same protocol was applied on both groups which was two doses of ReceptalÂ® (10Î¼g GnRH analogue) with 10 days apart and exogenous progesterone (PRID) insertion at day zero and was removed at day 10. Blood samples were taken several days for analysing Follicle-stimulating hormone (FSH), Progesterone (P4) and Estradiol (E2). Also, Follicular Size was measured using ultrasound. Significant differences were obtained in FSH, P4 and E2 along days of treatment. Moreover, multiparous had higher levels of FSH and E2 than primiparous. On the other hand, no significant difference in P4 level was recorded between groups. In general, treatment induced significantly a new follicular wave and stimulates follicle growth from 8.406 mm (day13) up to 12.791 mm (day 15 of PRID insertion), nevertheless, no significance in follicular size between groups was observed. She-camels in both groups revealed a noticed response to treatment protocol which was observed via estrous signs. Pregnancy rate doesn't reveal a significant difference between groups. We can conclude that, a combination of 1.55gm of exogenous P4 and two doses of 10Âµg GnRH analogues can enhance emergence of follicular development up to pre ovulatory size and significantly alter hormonal profile of primiparous and multiparous she camels with inactive ovaries.